Introduction to the physics of interstellar dust - Krugel, Endrik (New York, Taylor & Francis, 2008)
Streamlining the extensive information from the original, highly acclaimed monograph, this new An Introduction to the Physics of Interstellar Dust provides a concise reference and overview of interstellar dust and the interstellar medium. Drawn from a graduate course taught by the author, a highly regarded figure in the field, this all-in-one book emphasizes astronomical formulae and astronomical problems to give a solid foundation for the further study of interstellar medium. Covering all phenomena associated with cosmic dust, this inclusive text eliminates the need to consult special physical literature by providing a comprehensive introduction in one source. The book addresses the absorption and scattering of dust, its creation in old stars, as well as emission, cohesion, and electrical charge. With strong attention to detail, the author facilitates a complete understanding from which to build a more versatile application and manipulation of the information. Providing insightful explanations for the utilization of many formulae, the author instructs in the effective investigation of astronomical objects for determining basic parameters. The book offers numerous figures displaying basic properties of dust such as optical constants, specific heat, and absorption and scattering coefficients making it accessible for the reader to apply these numbers to the problem at hand. There is an extensive section and comprehensive introduction to radiative transfer in a dusty medium with many practical pieces of advice and ample illustrations to guide astronomers wishing to implement radiative transfer code themselves.An unparalleled amount of astronomical information in an accessible and palatable resource, An Introduction to the Physics of Interstellar Dust provides the most complete foundational reference available on the subject.
Bibliography 377-380p; Index 381-387p.
Keywords: Cosmic dust; Interstellar matter; Physics